EFEKTIVITAS PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA STATISTIC BALL DENGAN MODEL INQUIRY - Dewi Herawati; Shoffan Shoffa; Achmad Hidayatullah (Universitas Islam Malang, 2020)
This research begins from the low student’s learning result, because in the mathematic’s learning process students aren’t actively involved and learning process more focus to teacher (teacher centered), so teacher more dominates and becomes the center of attention in learning activity. This proves that less effective learning process at school. The purpose of this research is looking for the effectivity of mathematics learning using statistic ball media with inquiry model at mathematics learning VIII class junior high school spesifically for statistic lesson. Type of this research is descriptive quantity research. Research design used one group pretest posttest design. Research sample is 30 students class VIII-C Muhammadiyah 15 Junior High School, Surabaya. Research data is observation to find out students activities and teachers ability to manage learning, questionnaire to find out student’s response, and test question in the form of essay for measure mathematic ability on statistic learning. The result of this research shows that teacher’s ability on manage learning get a very good category, student’s activity get a very active criteria, completeness of student’s learning result shows that 80% from all students reach KKM. Student’s response to this mathematics learning, students show a positive response. So, application of mathematic learning models used statistic ball media with inquiry model effective use on mathematic learning at student grade VIII-C Muhammadiyah 15 Junior High School, Surabaya.